Haptic feedback as affective amplifier: enhanced fear perception affects cognitive performance and avoidance actions in VR height exposure - Lin Cong; Lin Cong; Shan Cheng; Chaolin Teng; Kaiwen Xiong; Meiqing Huang; Jin Ma; Wendong Hu; Jianqi Wang; Weitao Dang; Kewei Sun; Taihui Zhang (Frontiers in Psychology, 2025)
Haptic feedback serves as a potent affective amplifier in virtual reality (VR), intensifying threat perception to influence emotional intensity. This study investigated how haptic-enhanced fear stimuli (delivered through platform shaking during VR height exposure) impair cognitive performance and avoidance actions. Twenty male participants with self-reported fear of heights were subjected to four emotion-inducing conditions: neutrality, ground, stationary, and shaking, with each condition separated by 1 week. We have multimodal assessed of physiological (EEG, peripheral physiological arousal), behavioral (movement distance, eye movement), and cognitive performance (nine-light task accuracy rates and reaction time) during fear induction. Results revealed significant declines in task accuracy and prolonged reaction times during the shaking condition, indicating resource competition where threat processing impaired goal-directed motor execution. The decreased movement distance and increased pupil dilation indicated the initiation of an automatic defense response. Furthermore, physiological markers confirmed amplified this threat processing. The increased heart rate and elevated β band activity in EEG, indicating heightened cortical engagement with fear stimuli. The integration of physiological, behavioral, and subjective measures provides a mechanistic model for affective-motor competition, demonstrating how somatic threat cues translate into altered actions.